Regulatory Roles of Invariant Natural Killer T Cells in Adipose Tissue Inflammation: Defenders Against Obesity-Induced Metabolic Complications - Park, Yoon Jeong; Park, Jeu; Huh, Jin Young; Hwang, Injae; Choe, Sung Sik; Kim, Jae Bum (Frontiers in Immunology, 2018)
Adipose tissue is a metabolic organ that plays a central role in controlling systemic energy homeostasis. Compelling evidence indicates that immune system is closely linked to healthy physiologic functions and pathologic dysfunction of adipose tissue. In obesity, the accumulation of pro-inflammatory responses in adipose tissue subsequently leads to dysfunction of adipose tissue as well as whole body energy homeostasis. Simultaneously, adipose tissue also activates anti-inflammatory responses in an effort to reduce the unfavorable effects of pro-inflammation. Notably, the interplay between adipocytes and resident invariant natural killer T (iNKT) cells is a major component of defensive mechanisms of adipose tissue. iNKT cells are leukocytes that recognize lipids loaded on CD1d as antigens, whereas most other immune cells are activated by peptide antigens. In adipose tissue, adipocytes directly interact with iNKT cells through presenting lipid antigens and stimulate iNKT cell activation to alleviate pro-inflammation. In this review, we provide an overview of the molecular and cellular determinants of obesity-induced adipose tissue inflammation. Specifically, we focus on the roles of iNKT cell-adipocyte interaction in maintaining adipose tissue homeostasis as well as the consequent modulation in systemic energy metabolism. We also briefly discuss future research directions regarding the interplay between adipocytes and adipose iNKT cells in adipose tissue inflammation.